Controlling Staphylococcus Aureus And Methicillin Resistant Staphylococcus Aureus Using Diarrheal Medicine Herbs Of Maek Society - Zaunit, Muthia Miranda; Febria, Fuji Astuti; Bakhtiar, Amri (Metamorfosa: Journal of Biological Sciences, 2019)
The aims of this research are to analyze the phytochemical contents and to know the antibacterial potential of medicines herbs of Maek Society in controlling  S. aureus and Methicillin Resistant Staphylococcus aureus   (MRSA). This research is conducted on March – July 2017 in Biota Sumatera Laboratory and Microbiology Research Laboratory of Biology Departement, Andalas University. The method is experiment with five treatments of concentration against two bacterias test. The result showed that phytochemical test of medicine herbs extract contains alcaloids and phenol. All of the extracts concentration able to control S. aureus and MRSA. Antibacteria activity of the medicine herbs against S. aureus is stronger than againts MRSA. The highest diameter of the inhibitory zones extract against     S. aureus is 12,98 ± 1,29  mm and against MRSA is 12,56 ± 0,38 mm. Key words: Staphylococcus aureus, MRSA, medicine herbs, phytocemical test, antibacteria